ASSESSMENT OF BIOCHEMICAL PARAMETERS IN PREGNANT WOMEN WITH METABOLIC DISORDERS: A COMPARATIVE STUDY - S. G. Dzugkoev; A. I. Tedtoeva; F. S. Dzugkoeva; I. V. Mozhaeva; O. I. Margieva (Акушерство, гинекология и репродукция)
Objective: еvaluation of lipid metabolism, lipid peroxidation (LPO) and antioxidant system (AOS) in pregnant women with various metabolic disorders. Materials and methods. This study was conducted in pregnant women with no known metabolic disorder, in those with the symptoms of metabolic syndrome and in women with gestational diabetes mellitus. Results. We found evidence for activation of LPO in pregnant women with impaired glucose metabolism; the LPO developed on the background of decreased activity of AOS enzymes. As proposed, the active oxygen species and the LPO products caused a reduction in the level of nitric oxide (NO) - a major vasodilating substance. The resulting vasoconstriction might lead to hypoxia with its negative impact on fetus development. Conclusion. Based on the obtained data we recommend using the parameters of LPO-AOS and the markers of endothelial NO-production as additional laboratory tests in pregnant women with gestational diabetes mellitus and metabolic syndrome.